Transformador monofásico: comparativo de materiais para os enrolamentos - Marchese, Abramo Ribeiro (2018)
The cost of electrical materials increasingly becomes more expensive because the inflation and the devaluation of the real against the dollar. It is important to review the costs of manufacturing equipment and the materials used in transformers, which are found in many equipment in both electronics and in the electric power distribution and transmission. Aluminum has higher electrical resistance and lower electrical conductivity, so it is necessary to study the feasibility of using aluminum windings in transformers where the industry still produces copper windings. The study verify if aluminum is capable of replacing copper in order that a transformer with aluminum windings meets the same requirements as transformer with copper windings. Will be verified if this replacement will have significant impacts on losses and in the core size. The present work aims to write an algorithm to calculate transformers, design and produce two transformers prototypes: with aluminum windings and the other with copper windings. Measurements will be made in order to provide a comparison between prototypes and between design data to validate the calculus.